1987
DOI: 10.1002/1097-0142(19870715)60:2<248::aid-cncr2820600223>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Family history of colorectal cancer as a marker of potential malignancy within a screening program

Abstract: Epidemiologic studies have shown that asymptomatic adult relatives of colorectal cancer patients are at increased risk for developing this tumor. A prospective, published pilot study confirmed this added risk and demonstrated the importance of the family history of cancer as a marker of potential malignancy. The study group was enlarged to include 471 asymptomatic adult, first degree relatives of patients having large bowel neoplasia (cancer or adenomatous polyps) but without polyposis syndromes. These first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
1
5

Year Published

1987
1987
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(38 citation statements)
references
References 26 publications
2
30
1
5
Order By: Relevance
“…In studies in which yield has been broken down by age, findings have been similar to our own, with the incidence of neoplasia rising from 0–4.3% under the age of 40 years to 16–32% over the age of 60 years 1315 18 21 Comparing yield with that found in the general population is important, particularly at lower levels of familial risk. Yield obtained with 60 cm flexible sigmoidoscopy was 5.7% in a population of mean age 55 years 27.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In studies in which yield has been broken down by age, findings have been similar to our own, with the incidence of neoplasia rising from 0–4.3% under the age of 40 years to 16–32% over the age of 60 years 1315 18 21 Comparing yield with that found in the general population is important, particularly at lower levels of familial risk. Yield obtained with 60 cm flexible sigmoidoscopy was 5.7% in a population of mean age 55 years 27.…”
Section: Discussionsupporting
confidence: 81%
“…Yield obtained with 60 cm flexible sigmoidoscopy was 5.7% in a population of mean age 55 years 27. Although all controlled studies have shown a higher yield in family members than controls,9 18 21 25 even in one of the larger studies this has failed to reach statistical significance 21…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…At first glance our results might appear at odds with clinical and epidemiological studies which show an almost twofold increase in the risk of CRC and adenomas between patients and first-degree relatives (3, 5, 7-10). However, these studies are not uniformly confirmatory and inconsistences are common (3)(4)(5)(6)(7)(8)(9)(10). Further complicating the picture is the lack of a genetic explanation to account for a hereditary risk in late-onset CRC (17,18).…”
Section: Discussionmentioning
confidence: 99%